Merancang Nilai Ambang Batas Seleksi Kompetensi Bidang Pengadaan PPPK: Studi Empiris Pada Jabatan Fungsional Kementerian Kelautan Dan Perikanan - Dida Daniarsyah; Fionera Santuna Indah (Universitas Serang Raya, 2021)
This article discusses how to design the passing grade of field competency selection (SKB) for the needs of the recruitment process for prospective Government Employees with a Work Agreement (PPPK) who will fill the formation of Functional Positions at the Ministry of Maritime Affairs and Fisheries (KKP). The absence of government guidelines in designing the passing grade value for PPPK candidates triggers Ministries/Institution to design the passing grade value SKB as a necessity in the recruitment process. Research through empirical studies designed the passing grade value SKB for the KKP Functional Position using the Ebel method approach, the Trial Method, and the Judgment Method. The results of the study reveal that the technique of designing the the passing grade value SKB is very dependent on the technical policy of preparing questions so that it is easier, more precise in considering the standard setting method approach or determining the method approach to designing the passing grade value SKB.The passing grade value SKB for the Functional Position of the KKP Guiding Agency based on the three methods obtained results that have close values ​​or differences that are not too significant. The range of values ​​between the interval 45 – 55 absolute numbers. This data indicates that between the technical policy of problem formulation and determining the Ebel method as an approach to the standard setting method in designing the passing grade value is correct and inline. Keywords: PPPK, Passing Grade Value, Methods Approach